2020
DOI: 10.1097/md.0000000000023418
|View full text |Cite
|
Sign up to set email alerts
|

PERCEPTION Trial protocol

Abstract: Background: Triple negative breast cancer affects 10% to 20% of all women diagnosed with breast cancer. Due to its characteristics, treatment strategies are limited and metastatic recurrences are common in the first 5 years after treatment. However, not all patients affected by this disease develop metastases. Tumor-infiltrating lymphocytes have shown to be reliable predictive biomarkers of treatment response and metastatic recurrences. However, we need to develop simpler and faster ways to predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
(15 reference statements)
2
3
0
Order By: Relevance
“…One study by Lee et al ., 30 which included pretreatment and postchemotherapy NLR, reported a decrease in NLR and the same/increased TILs to be associated with prolonged DFS, but correlation analysis between NLR wih TILs was not performed. An ongoing clinical trial aiming to evaluate NLR versus TILs is currently under way 31 . Similar to previous studies, TILs on H&E slides in the current study were not associated with pretreatment NLR, but demonstrated a negative correlation to late postsurgery NLR.…”
Section: Discussionsupporting
confidence: 84%
“…One study by Lee et al ., 30 which included pretreatment and postchemotherapy NLR, reported a decrease in NLR and the same/increased TILs to be associated with prolonged DFS, but correlation analysis between NLR wih TILs was not performed. An ongoing clinical trial aiming to evaluate NLR versus TILs is currently under way 31 . Similar to previous studies, TILs on H&E slides in the current study were not associated with pretreatment NLR, but demonstrated a negative correlation to late postsurgery NLR.…”
Section: Discussionsupporting
confidence: 84%
“…One study by Lee et al (30) which included pretreatment and post-chemotherapy NLR reported that a decrease in NLR and same/increased TILs to be associated with prolonged DFS, but correlation analysis between NLR with TILs was not performed. An ongoing clinical trial aiming to evaluate NLR vs. TILs is currently underway (31). In the current study, TILs on H&E slides, similar to previous studies, was not associated with pre-treatment NLR, but demonstrated negative correlation to late post-surgery NLR.…”
Section: Discussionsupporting
confidence: 83%
“…Some studies reported the association of PLR increase and pCR, whereas in others lowering of PLR was favorable for good response ( 49 , 50 ). To better determine the time point during NACT at which the PLR value is most predictive, as well as to determine the predictive value of PLR change between different time-points during NACT, prospective studies are needed, like the one our group has recently initiated (PERCEPTION trial, NCT04068623) ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the findings of our study need to be validated in larger patient cohorts. In this line, our group has recently started a prospective translational trial, PERCEPTION, whose main objective is evaluation of predictive and prognostic value of blood cell counts, NLR, PLR and TILs, before, during and after anthracycline/taxane-based NACT in TNBC patients ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation